Personal utility is inherent to direct-to-consumer genomic testing - Chung, Matthew Wai Heng (Journal of medical ethics, 2016)
People for and against direct-to-consumer (DTC) genomic tests are arguing around two issues: first, on whether an autonomy-based account can justify the tests; second, on whether the tests bring any personal utility. Bunnik et al, in an article published in this journal, were doubtful on the latter, especially in clinically irrelevant and uninterpretable sequences, and how far this claim could go in the justification. Here we argue that personal utility is inherent to DTC genomic tests and their results. We discuss Bunnik et al's account of personal utility and identify problems in its motivation and application. We then explore concepts like utility and entertainment which suggest that DTC genomic tests bring personal utility to their consumers, both in the motivation and the content of the tests. This points to an alternative account of personal utility which entails that entertainment value alone is adequate to justify DTC genomic tests, given appropriate strategies to communicate tests results with the consumers. It supports the autonomy-based justification of the test by showing that DTC genomic test itself stands as a valuable option and facilitates meaningful choice of the people.